GENDER DIFFERENCES OF ARTERIAL HYPERTENSION AND ANTIHYPERTENSIVE THERAPY - L. I. Katelnitskaya; L. A. Haisheva (Рациональная фармакотерапия в кардиологии)
Aim. To study gender differences of endothelial vasomotor function and pulse wave velocity (PWV) in patients with arterial hypertension (HT) and to evaluate effects of amlodipine (Normodipine, Gedeon Richter) on these parameters.Material and methods. 57 patients with HT of 1-2 stages were involved in the study. Patients were randomized to 4 groups: women under 50 y.o. (group 1), women older than 60 y.o. (group 2), men under 50 y.o. (group 3) and men older than 60 y.o. (group 4). Endothelium vasomotor function was estimated by ultrasonography. PWV was estimated by volume sphygmography. Patients received antihypertensive therapy with amlodipine during 12 weeks.Results. The lowest levels of systolic blood pressure (BP), normal endothelium function and PWV were observed in women with normal menses. The highest levels of pulse BP were found in menopausal women. Amlodipine monotherapy had better antihypertensive effect in women than in men. BP target levels were reached in 60% of amlodipine treated women. Besides amlodipine improved vascular endothelial function.Сonclusion. Disorders of endothelial function and PWV begin later in women than in men, however after menopause the rate of these disorders development in women is faster than in men of similar age.